Molecular comparison of chili populations (Capsicum spp.) from Tabasco and Chiapas, Mexico (Bioagro, 2020)
Based on the importance of chile in the Southeast of Mexico, the objectives of this research were to characterize molecularly, and estimate the polymorphism and genetic structure of 21 populations of Capsicum spp. of Tabasco and Chiapas States, Mexico. After 40 days of germination of the seeds collected, two young leaves of each population were cut per each of 10 plants.  The 20 leaves were mixed and three samples of 0,5 g were taken to extract the DNA. Four microsatellite markers (SSR) to determine the genetic diversity. A total of 229 alleles were detected, and 70 were polymorphics. The marker Hpms1-106 detected 38.8 % polymorphism, and HpmsCaSIG-19 the lowest polymorphism (20,55 %). The AMOVA explained 13,0 % of the variability among populations, and individuals within populations explained the remaining 87,0 %. The statistics FST = 0.176, showed a large differentiation between populations. The FIS = -0,448 showed an excess of heterozygous in populations, and the FIT = -0,193 showed that individuals in each population have moderate non-random mating effect between them. Cluster analysis grouped all evaluated chili populations into six clusters. The cluster I grouped 13 populations, some of  these such as Amashito Cerro Blanco and Colmillo de Lagarto El Porvenir showed to be the most genetically similar.  In the cluster VI, Pico de Paloma Miahuatlán showed to be different from the rest of populations. Microsatellite markers were useful to analyze the genetic diversity of these chili populations.
Keywords: C. annuun; C. frutescens; genetic diversity; molecular analysis; molecular markers; populations structure